Accelerated design of high-strength refractory multi-principal element alloys from first-principles calculations - Fu, Yuling; Liu, Pengjing; Zhang, Hualei; Ding, Xiangdong; Sun, Jun (Journal of materials research and technology, 2025)
To rapidly develop high-strength refractory multi-principal element alloys (RMPEAs), we systematically calculate elastic moduli and mechanical properties for a series of body-centered-cubic (bcc) RMPEAs using the first-principles method. By analyzing equiatomic V33Nb33Mo34 and V25Nb25Mo25X25 (X = Al, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, and W) bcc RMPEAs, we discover that the product of shear modulus (G) and electronegativity difference (δχ), i.e., G × δχ, accurately predicts yield strength (σy). This criterion outperforms other empirical parameters such as valence electron concentration (VEC), G, or δχ alone. Specifically, higher G × δχ correlates with higher σy. The σy of V25Nb25Mo25Cr25 exceeds that of other equiatomic alloys, agreeing with existing experiments, thereby validating the reliability of our approach. Following the G × δχ criterion, we further design non-equiatomic V50-xNb50-xMoxCrx bcc RMPEAs based on V25Nb25Mo25Cr25. We identify V15Nb15Mo35Cr35 as a target RMPEA, which exhibits the highest σy and good high-temperature softening resistance among all considered bcc RMPEAs. The universality of the G × δχ criterion is confirmed not only by current calculations but also by available experiments, as evidenced by the maximum Pearson correlation coefficient between σy and G × δχ. This work provides an effective paradigm for discovering high-strength bcc refractory alloys by strategically optimizing the G × δχ metric. TheG×δχcriterion accelerates the discovery of high-strength bcc RMPEAs. By systematically investigating equiatomic V33Nb33Mo34 and V25Nb25Mo25X25 bcc RMPEAs, it is revealed that the product of shear modulus (G) and electronegativity difference (δχ), i.e., G × δχ, serves as an effective predictor of yield strength (σy). Specifically, higher G × δχ correlates with higher σy. The σy of V25Nb25Mo25Cr25 surpasses that of other equiatomic alloys, agreeing with existing experiments. Guided by the G × δχ criterion, we identify V15Nb15Mo35Cr35 as a target RMPEA, which exhibits the highest σy among all considered bcc RMPEAs. Additionally, the observed decrease in σy may partially arise from the reduction in ΔσNb and ΔσCr. Importantly, the universality of the proposed G × δχ criterion is validated by both our calculations and existing experiments ranging from ternary to senary alloys, including Ti–Zr-based, Ti–Zr-Hf-based, V–Nb-based, and V–Nb–Mo-based systems. [Display omitted]